EFFECTS OF ACCOUNTING EARNINGS AND AGRIBUSINESS EXPANSION ON GROSS DOMESTIC PRODUCT - Yuliyanti; Moh Rudi Nugroho; Slamet Haryono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study aims to analyze the impact of accounting earnings, agricultural policies, and agribusiness expansion through stock market returns on economic growth in Indonesia, with Agricultural Gross Domestic Product (AGDP) as an intervening variable. Its usage is based on the difference in levels between the independent variables as micro-level, and Gross Domestic Product (GDP) as macro-level. The data were panel data from 32 out of 68 companies in the agricultural and agribusiness sectors listed on the Indonesia Stock Exchange (IDX) during the period of 2015–2023. The analysis was conducted with hypothesis testing and the Sobel test to examine the direct and indirect effects of the independent variables on economic growth. The results show that accounting earnings and stock market return do not have a significant direct effect on economic growth. However, accounting earnings have a significant indirect effect on economic growth through AGDP as the intervening variable. Agricultural policies are indicated to have a significant effect on economic growth directly and indirectly. AGDP also plays an important role in promoting inclusive and sustainable economic growth in Indonesia.